„Girls to the Girl’s Room, Boys to the Boy’s Room”. The Visible and Invisible Pedagogy in Pre – School Education from the Perspective of Basil Bernstein - Szczepaniak, Colette (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
The author, wanting to identify means of socializing girls and boys for performing specific gender roles within pre-school education, conducted research using the direct observation method in one of the groups of five-year-olds in a public kindergarten in a city of 40,000. Using Basil Bernstein’s theory of visible and invisible pedagogy, she recognized in what teachers’ activities one of the types of this pedagogy is revealed and how it affects the process of socialization of children to take specific roles due to gender. The teacher who used visible pedagogy clearly showed the children where the boys’ and girls’ “places” were, whereas teacher 2, using invisible pedagogy, did not interfere with the children’s individual choices regarding playing and types of toys.